Modification of Ag3PO4 surface using a nanosilver solution prepared under sunflower seed extract - Azmi, Vania Amelia; Sulaeman, Uyi; Larasati, Rini; Hermawan, Dadan; Asnani, Ari; Isnaeni, Isnaeni; Yin, Shu (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Designing new properties of Ag3PO4 photocatalysts is challenging as the Ag3PO4 surface is highly susceptible to photocorrosion. This study aims to improve the properties of Ag3PO4 by modifying its surface using a nanosilver solution prepared under sunflower seed extract. This photocatalyst was prepared by chemical coprecipitation. Based on XPS analysis, the interaction of nanosilver solution with the Ag3PO4 surface significantly affected the P 2p chemical state and decreased the Ag/P atomic ratio of Ag3PO4. The modification of the Ag3PO4 surface by nanosilver solution resulted in the formation of silver vacancy defects and the incorporation of Ag nanoparticles (AgNPs) on the Ag3PO4 surface. This new design of Ag3PO4 showed a remarkable photocatalytic reaction for Rhodamine B oxidation and antibacterial activity under blue light irradiation. The photocatalytic reaction was mainly driven by forming superoxide anion radicals and hole species. This phenomenon can provide a new direction in the improvement of the photocatalytic ability of Ag3PO4 through a natural plant material approach.